Pendidikan Agama Kristen Terhadap Keluarga Pendeta Gereja Masehi Injili di Minahasa Dan Dampaknya Bagi Pelayanan Gereja Masa Kini - Tamaka, Melki (Educatio Christi, 2020)
Education Christian Religion to the family pastor to be an example and exemplary in the life of the church. But many parents pastors are too busy in the task and service so there is a forgotten education this faith and the result are children neglected as well as a negative impact for the church services.